Tourism Development Strategy Sustainable Environmental Insight In Kampar District, Riau Province - Syafrial, Doni; ., Zulkarnain; Yoswati, Dessy; Nasution, Belli (Journal of Ecohumanism, 2024)
The exploitation of various tourism potentials in Kampar Regency is still not maximized; incredibly natural attractions such as lakes and playgrounds, history and education, as well as folk crafts. In general, the problem that causes the low number of tourist visits to tourist places is tourism management that has not been optimally packaged so that tourists are less interested in visiting; this is evident from the unavailability of the typical souvenir market for Kampar Regency, the unavailability of adequate transportation facilities, and the lack of promotion. Go out. Based on these potentials and problems, researchers need to conduct further research related to tourism development strategies, focusing on studying tourism resource management and internal and external factors that influence its development. Through the results of the data collection obtained, the researcher can carry out an analysis in the form of a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis so that alternative strategies and patterns of developing tourist destinations will be arranged that prioritize ecological, cultural sustainability and increase the income of local communities. This study used saturated sampling techniques with data collection through interviews, observations, and questionnaires. The role of the Government, private sector, and the community contributes to the development of tourist destinations in Kampar Regency. During its existence, POKDARWIS has made various efforts to sustainably change and improve the quality of management of tourist destinations. Most of those not involved with internal issues have made various developments and changes related to the tourism products offered to enhance the quality of service.